PROS1 novel splice-site variant decreases protein S expression in patients from two families with thrombotic disease - Menezes, J (2017)
Our results prove that c.1871-14T>G is causative of type I PS deficiency, highlighting the importance of performing mRNA-based studies in order to evaluate variants pathogenicity. We evidence the increased risk of venous thromboembolism associated with this cryptic splice-site variant if present in patients with PS deficiency.